Forensic CBT : a handbook for clinical practice - Tafrate, Raymond Chip.; Mitchell, Damon (Chichester, West Sussex : Wiley, 2013)
-- Is an edited collection that represents the first authoritative resource on the utilization of CBT strategies and techniques for offender clients.Features contributions from leaders of the major schools of CBT on the treatment of antisocial personality patterns as well as anger, interpersonal violence, substance abuse, and sexual aggressionAddresses modified CBT approaches for female, juvenile, and culturally diverse forensic populationsCovers emerging areas of forensic practices, including the integration of motivational interviewing and strength-based approachesIncludes an assortment of worksheets, handouts, and exercises for practitioners to use with their clients.
About the editors and contributors -- Preface -- Introduction : critical issues and challenges facing forensic CBT -- Practitioners / Damon Mitchell, David Simourd, & Raymond Chip Tafrate -- Criminal behavior and antisocial patterns : conceptualizing treatment from different cbt perspectives -- Traditional and next generation CBT models -- Traditional cognitive behavioral therapy models for antisocial patterns / Lori Seeler, Arthur Freeman, Raymond DiGiuseppe, & Damon Mitchell -- Act for the incarcerated / Jai Amrod & Steven C. Hayes -- Schema therapy for aggressive offenders with personality disorders / Marije Keulen-de Vos, David P. Bernstein, & Arnoud Arntz -- Criminal thinking models -- An overview of strategies for the assessment and treatment of criminal thinking / Daryl G. Kroner & Robert D. Morgan -- Applying cbt to the criminal thought process / Glenn D. Walters -- Training community corrections officers in cognitive behavioral intervention strategies / Tanya Rugge & James Bonta -- Cbt interventions for common criminal justice problem areas -- Two perspectives on the treatment of anger -- Anger management for offenders : a flexible CBT approach / Howard Kassinove & Michael J. Toohey -- Contextual anger regulation therapy (CART) : an acceptance-based treatment for domestic and non-domestic violent offenders / Frank L. Gardner & Zella E. Moore -- Two perspectives on the treatment of intimate partner violence -- CBT for perpetrators of intimate partner violence : the "I3" approach / Christopher I. Eckhardt, Cory A. Crane, & Joel G. Sprunger -- A couple-based violence reduction approach to curbing intimate partner assault / George Ronan, Kimberly Maurelli, & Krista M. Holman -- Two perspectives on the treatment of addictions -- An integrated rebt approach to the treatment of addicted offenders / F. Michler Bishop -- Social and community responsibility therapy (SCRT) : a cognitive-behavioral model for the treatment of substance abusing judicial clients / Ken W. Wanberg & Harvey B. Milkman -- Two perspectives on the treatment of sexual aggression -- Balancing clients' strengths and deficits in sexual offender treatment : the rockwood treatment approach / William L. Marshall & Matt D. O'Brien -- Recidivism risk reduction therapy (3RT) : cognitive-behavioral / approaches to Treating Sexual Offense Behavior / Jennifer Wheeler & Christmas Covell -- Tailoring CBT to special forensic populations -- Advancing the use of CBT with justice-involved women / Marilyn Van Dieten & Erica King -- CBT with juvenile offenders : a review and recommendations for practice / Eva Feindler & Alison M. Byers -- Culturally responsive CBT in forensic settings / Andrew Day -- Emerging ideas for practice -- Session-by-session assessment of client participation and progress / David Simourd -- Integrating motivational interviewing with forensic CBT : promoting treatment engagement and behavior change with justice-involved clients / Raymond Chip Tafrate & Jennifer D. Luther -- Integrating strength-based practice with forensic CBT : the good lives model of offender rehabilitation / Clare-Ann Fortune & Tony Ward -- Treating depression and PTSD behind bars : an interaction schemas approach / Key Sun -- Conclusions -- Forensic CBT : five recommendations for clinical practice and five topics in need of more attention / Raymond Chip Tafrate, Damon Mitchell, & Raymond W. Novaco.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Forensic sciences; Cognitive therapy; Criminal psychology; Cognitive Therapy; SOCIAL SCIENCE -- Penology; Cognitive therapy; Criminal psychology; Forensic sciences; Electronic books